Corporate governance and risk : - Shaw, John C. (John Wiley & Sons, 2003)
Corporate Governance and Risk introduces a new framework for thinking about governance and risk as well as a process for its implementation. This book provides a unique perspective on this topic–taking you through the detailed steps required to understand and act upon what needs to be done in order for organizations to be more effective in this new world of governance and risk.